Medieval Sufi Charitable Institutions Sponsored by the State: A Comparative View in the Maghrib and Anatolia - Almela, Iñigo (Muqarnas, 2024)
In recent decades scholarship has shown a special interest in Sufism as a component of Islamic society; nevertheless, the study of its material culture has advanced more slowly, impeding a better understanding of the spaces associated with it. In light of the two different models of zāwiya that other researchers have previously identified in the Middle East—more modest ones undertaken by individuals and monumental ones sponsored by the state—I have so far been able to recognize a similar dichotomy in al-Maghrib al-Aqsa. This article, however, examines the two aforementioned models, placing them on an even broader geographical framework that allows for a comparison between two extremes of the Islamic Mediterranean, the Maghrib and Anatolia, revealing common patterns as well as characteristics peculiar to each.